Contact Tracing Apps in Asean : A Threat to Privacy and Personal Data - Sihombing, Agung Kurniawan; Bratajaya, Yogi (Kathmandu School of Law Review, 2020)
On March 11 2020, the World Health Organization (WHO) officially categorized the Coronavirus disease (COVID-19) as a global pandemic. The rapid spread of COVID-19 prompted governments all around the world to take steps toward controlling the pandemic and its significant socio-economic impacts. Digital technology has been relied upon to provide innovative solutions to aid efforts of stopping the spread of COVID-19. One such innovation is the development and implementation of contact tracing applications or apps. The use of these apps allows public health authorities to track confirmed cases of COVID-19 and mitigate its transmission. However, as useful as they may be, there exists a well-grounded fear that contact tracing apps may be used as a tool to broaden government surveillance powers. This is especially true among member nations of the Association of Southeast Asian Nations (ASEAN), where domestic regulations guaranteeing the right to privacy and protection of personal data are relatively weak. Additionally, ASEAN lacks a comprehensive and strong regional mechanism for the protection of human rights and personal data. This paper aims to analyze the implementation of contact tracing apps in ASEAN member states, whether its implementation fulfills the international standards of the protection of the right to privacy and personal data, as well as provide recommendations to ensure that countries do not spiral towards a state of unrestricted government surveillance.